Factor affecting radiation exposure in building of UiTM Perak/ Adibah Mohd Noor ... [et al.] - Mohd Noor, Adibah; Mohamed Khir, Northaqifah Hasna; Sukri, Nur Syafika; Azma Azmi, Nor Arfawati; Hanapi, Siti Nur Hazirah; Mohamad Mizam, Noor Anis (2023)
The paper consider the radiation study in UiTM Tapah building. The objective of this study is to measure radiation dosage in UiTM Tapah building and differentiate the radiation by building design and variable time. The radiations were measured using a survey meter in terms of μSv/hour. Four different buildings at UiTM Tapah have been selected and survey meter equipment is used to measure the radiation dosage in the buildings. Each place of building is measured in a three points of locations with a distance of 1 meter of each point. The reading was taken 1 meter from the ground and preparation was setup before the reading obtained. The highest radiation observed is 0.770 μSv/hour at PTAR library and the lowest is 0.350 μSv/hour at College Gamma. The type of building design and variable time give the significant differences values of radiation at UiTM Tapah buildings.